Might Spinoza be Considered more as an Exponent of the Oriental Enlightenment, than as an Exponent of the Western Enlightenment? - van Reijen, Miriam (Araucaria, 2018)
In philosophy the relation between reason or wisdom and happiness is a returning theme, and so it is for Spinoza. In his Ethics he describes a path to happiness, but he states that reason often fails to reach it, because of the power of the passions. Only reason with an affective loading can be decisive. For this way of knowing Spinoza uses the word ’intuitive’ knowledge. This has led to some interpretations of Spinoza’s philosophy as mysticism. In my contribution I suggest that Spinoza who is sometimes considered as belonging to the Western Enlightenment, because of his emphasis on reason, can be considered also as a representative of the eastern enlightenment, because of the great value he attach to the intuitive knowledge.